2004
DOI: 10.1152/ajpcell.00158.2004
|View full text |Cite
|
Sign up to set email alerts
|

ATP-induced mitogenesis is mediated by cyclic AMP response element-binding protein-enhanced TRPC4 expression and activity in human pulmonary artery smooth muscle cells

Abstract: . ATP-induced mitogenesis is mediated by cyclic AMP response element-binding protein-enhanced TRPC4 expression and activity in human pulmonary artery smooth muscle cells. Am J Physiol Cell Physiol 287: C1192-C1201, 2004. First published June 30, 2004 doi:10.1152/ajpcell.00158.2004.-Extracellular ATP and intracellular cyclic AMP response element-binding protein (CREB, a transcription factor) promote cell proliferation in many cell types. The canonical transient receptor potential (TRPC) channels, which putativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
70
1

Year Published

2006
2006
2012
2012

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 95 publications
(77 citation statements)
references
References 78 publications
6
70
1
Order By: Relevance
“…This is likely to result in the loss of local control of total pulmonary vascular resistance in the lung. Low-dose ATP exerts mitogenic actions on human pulmonary artery smooth muscle cells, which may be relevant to the pathophysiological basis of severe pulmonary hypertension (Zhang et al, 2004b). Pulmonary hypertension can be a problem in patients with chronic obstructive pulmonary disease, which also has other causes; it is a life-threatening condition, and intravenous ATP infusion produces a significant decrease in mean pulmonary arterial pressure and pulmonary vascular resistance without changing the mean systemic arterial pressure (Brook et al, 1994).…”
Section: Hypertensionmentioning
confidence: 99%
“…This is likely to result in the loss of local control of total pulmonary vascular resistance in the lung. Low-dose ATP exerts mitogenic actions on human pulmonary artery smooth muscle cells, which may be relevant to the pathophysiological basis of severe pulmonary hypertension (Zhang et al, 2004b). Pulmonary hypertension can be a problem in patients with chronic obstructive pulmonary disease, which also has other causes; it is a life-threatening condition, and intravenous ATP infusion produces a significant decrease in mean pulmonary arterial pressure and pulmonary vascular resistance without changing the mean systemic arterial pressure (Brook et al, 1994).…”
Section: Hypertensionmentioning
confidence: 99%
“…ATP-induced mitogenesis in pulmonary artery SMC was shown to be mediated through CREB-induced TRPC4 gene transcription [162]. The in vivo relevance of TRPC isoform upregulation in human pulmonary artery SMC was observed in patients with idiopathic pulmonary arterial hypertension (IPAH), a disease characterized by excessive pulmonary artery SMC proliferation [43].…”
Section: Increased Expression Of Trpc Cation Channelsmentioning
confidence: 99%
“…In recent years, increasing number of studies have focused on the ion channels and pumps acquired or lost during VSMC switch to the synthetic phenotype and their role in proliferation [14,32,74,82]. The transcription factors that control the gene regulation of these proteins are starting to emerge [32,75,149,150,160,162]. However, the pro-proliferative downstream signaling pathways that they regulate remain poorly understood.…”
Section: Decrease Of Camkiiγ and Increase Of Camk Iiδmentioning
confidence: 99%
See 1 more Smart Citation
“…The SOCC has also been described in cultured human PASMCs and this conductance is insensitive to nifedipine, another dihydropyridine calcium channel antagonist, but fully inhibited by 0.5 mM Ni 2+ [30]. By means of siRNA or antisense oligonucleotides, the contribution of the canonical transient receptor potential (TRPC)1 and 4 proteins to endogenous SOCC was demonstrated in human cultured PASMCs [31,32]. Hence, in rat primary cultured PASMCs, we have previously shown that 5-HT activates a transient receptor potential vanilloid (TRPV)4-like calcium influx, potentially involved in PASMC proliferation [20].…”
Section: Effect Of 5-ht On Camentioning
confidence: 99%